The Ineffectiveness of "Effective" Management Strategies: First-Year Teachers, Behavior Management, and Identity. (2nd January 2016) - Dugas, Daryl
ABSTRACT: This article presents a research project that challenges the skills-based approach to classroom management in teacher education, particularly in the domain of responding to student misbehaviors. In 90-minute narrative-based interviews, 16 first-year Chicago Public School (CPS) teachers were prompted for narratives of their experiences responding to student misbehaviors. A thematic analysis of these interviews using a grounded theory methodology revealed three ways in which identity affected teachers' student behavior management decisions: (1) their desire to be seen as "a certain kind of teacher" by their students, (2) their desire to perceive themselves as a certain kind of person and teacher, and (3) identity concerns superseding effectiveness in teachers' selection of interventions. Implications of these findings are discussed. An experiential approach to identity development in teacher education is endorsed as a corrective to the predominantly skills-based approach to classroom management. An outline of a more coherent model of teacher identity is presented that may lend support and direction to this identity-based instruction and to future research in teacher identity.